Money Beliefs and Financial Behaviors: Development of the Klontz Money Script Inventory - Bradley Klontz; Sonya L Britt; Jennifer Mentzer; Ted Klontz (Journal of Financial Therapy, 2011)
Financial matters have been identified in the literature as a significant source of stress for individuals and families. However, little is known about the psychological issues related to money that may be contributing to individual and family problems. Using a sample of 422 individuals who identified their level of agreement on 72 money-related beliefs, this study identified four distinct money belief patterns. Three of these belief systems were significantly correlated with income and net worth. Demographic features associated with the four money belief scales are provided. The results of this study may be useful for practitioners interested in quickly and accurately identifying money beliefs in their clients that can have a negative impact on financial health.
Keywords: money disorder; money script; financial therapy; destructive money belief; financial health